IMPLEMENTING ISLAMIC MULTICULTURAL EDUCATION IN FOSTERING UNITY IN DIVERSITY: A CASE STUDY AT SD BRAWIJAYA SMART SCHOOL MALANG - Labib Mustofa; Ahmad Barizi; Mohammad Asrori (Muta'allim: Jurnal Pendidikan Agama Islam, 2026)
This study explores the implementation of Islamic multicultural education in fostering unity in diversity at the elementary level, with a particular focus on SD Brawijaya Smart School, Malang. Although the school is not an Islamic-based institution, the majority of its students are Muslim, creating a moral atmosphere where Islamic values coexist with the spirit of Bhinneka Tunggal Ika. Employing a qualitative descriptive approach, data were collected through interviews, observations, and document analysis involving teachers and school mentors. The study aims to understand how Islamic moral values, religious moderation initiatives, and inclusive school culture contribute to the development of tolerance and empathy among students in a multicultural environment. The findings indicate that Islamic values such as rahmah (compassion), ‘adl (justice), and ta’aruf (mutual understanding) are applied not only in religious instruction but also in daily school activities and institutional practices. Teachers play a pivotal role in contextualizing these values to encourage interfaith respect and civic responsibility. Furthermore, the school’s collaboration with the Ministry of Religious Affairs enhances teacher competence through religious moderation training, strengthening inclusivity and empathy in classroom practices. Cultural programs, such as Heroes’ Day celebrations featuring traditional attire, and participatory decision-making processes exemplify the creation of a school culture grounded in respect and cooperation. Overall, the study concludes that Islamic multicultural education can serve as an ethical and pedagogical bridge linking faith-based values with national ideals, thereby promoting unity, tolerance, and social harmony among young learners in Indonesia’s pluralistic society. Abstrak Penelitian ini bertujuan untuk mengeksplorasi penerapan pendidikan multikultural berbasis nilai-nilai Islam dalam menumbuhkan semangat unity in diversity di tingkat sekolah dasar, dengan studi kasus di SD Brawijaya Smart School, Malang. Meskipun sekolah ini bukan lembaga pendidikan berbasis Islam, mayoritas siswanya beragama Islam sehingga membentuk suasana moral yang selaras dengan semangat Bhinneka Tunggal Ika. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam, observasi, dan analisis dokumen yang melibatkan guru serta pembimbing sekolah. Tujuan penelitian adalah untuk memahami bagaimana nilai-nilai moral Islam, program moderasi beragama, dan budaya sekolah yang inklusif berkontribusi terhadap pembentukan sikap toleransi dan empati di lingkungan pendidikan yang majemuk. Hasil penelitian menunjukkan bahwa nilai-nilai Islam seperti rahmah (kasih sayang), ‘adl (keadilan), dan ta’aruf (saling mengenal) diterapkan tidak hanya dalam pembelajaran agama, tetapi juga dalam aktivitas sekolah dan praktik kelembagaan sehari-hari. Guru memiliki peran penting dalam mengontekstualisasikan nilai-nilai tersebut untuk menumbuhkan penghargaan lintas agama dan tanggung jawab kewargaan. Selain itu, kolaborasi sekolah dengan Kementerian Agama melalui pelatihan moderasi beragama meningkatkan kompetensi guru dalam menerapkan pembelajaran yang inklusif dan empatik. Program budaya seperti perayaan Hari Pahlawan dengan pakaian adat serta partisipasi guru dalam pengambilan keputusan mencerminkan terciptanya budaya saling menghormati dan bekerja sama. Secara keseluruhan, penelitian ini menyimpulkan bahwa pendidikan multikultural Islam berperan sebagai jembatan etis dan pedagogis antara nilai-nilai keagamaan dan ideal kebangsaan, yang berkontribusi dalam menumbuhkan persatuan, toleransi, dan harmoni sosial di lingkungan pendidikan dasar yang plural di Indonesia.